Kenilanthus, a new eudicot flower with tricolpate pollen from the Early Cretaceous (early-middle Albian) of eastern North America. Issue 3 (4th May 2017) - Friis, Else Marie; Pedersen, Kaj Raunsgaard; Crane, Peter R.
Abstract: A new Early Cretaceous flower, Kenilanthus marylandensis, is described from the fossil plant bearing sequence exposed in early-middle Albian Potomac Group sediments at the Kenilworth (Bladensburg) locality, Maryland, USA. The flower is small, actinomorphic, pentamerous, and isomerous, and contains both pistillate and staminate parts. The receptacle is slightly dome-shaped and bears one whorl of five tepals, with a possible additional whorl toward the outside, ten stamens in two whorls of five, and one whorl of five free carpels. Stamens have elongate, tetrasporangiate, dithecate anthers that arc slightly inwards towards the centre of the flower. Thecae protrude and are oriented outwards. Pollen grains are small, tricolpate and reticulate with a graded, heterobrochate reticulum and segmented, spiny muri. Carpels are elongate with abundant stomata on the outer surface, and each carpel has a broad oblique base. Ovules are numerous in each carpel and are borne on two marginal placentae that extend along either side of the ventral suture. Kenilanthus has a combination of features that occur among different early-diverging eudicot lineages, suggesting a phylogenetic position close to the base of the eudicot clade, but its precise phylogenetic position is difficult to resolve.